Nanofabrication : fundamentals and applications - Tseng, A. A. (World Scientific, 2008)
Many of the devices and systems used in modern industry are becoming progressively smaller and have reached the nanoscale domain. Nanofabrication aims at building nanoscale structures, which can act as components, devices, or systems, in large quantities at potentially low cost. Nanofabrication is vital to all nanotechnology fields, especially for the realization of nanotechnology that involves the traditional areas across engineering and science. This is the first book solely dedicated to the manufacturing technology in nanoscale structures, devices, and systems and is designed to satisfy the growing demands of researchers, professionals, and graduate students. Both conventional and non-conventional fabrication technologies are introduced with emphasis on multidisciplinary principles, methodologies, and practical applications. While conventional technologies consider the emerging techniques developed for next generation lithography, non-conventional techniques include scanning probe microscopy lithography, self-assembly, and imprint lithography, as well as techniques specifically developed for making carbon tubes and molecular circuits and devices.